Squamapion gardinii n. sp. from the Mediterranean Region and notes on some species belonging to the genus Squamapion Bokor, 1923 (Coleoptera, Apionidae) - Giusto, Carlo (Zootaxa, 2021)
Squamapion gardinii n. sp. from Italy, France and Spain (♂♀; type locality: Italy: Liguria: Genoa Province: Genova-Quinto al Mare: Rio San Pietro), associated with Thymus vulgaris L., is described. Squamapion solariorum (Wagner, 1908) n. stat., upgraded to species rank from subspecies of Squamapion consors (Desbrochers des Loges, 1875), is redescribed (holotype ♀ examined). New chorological records for Squamapion minutissimum (Rosenhauer, 1856) and Squamapion serpyllicola (Wencker, 1864) are also given; the latter species is recorded for the first time from Italy and Romania. A provisional key is provided to the species of Squamapion, related to Squamapion atomarium (Kirby, 1808), present in the Mediterranean region.